Classificando tipos de verbos na Língua Gestual Portuguesa - Martins, Mariana; Costa, Ângelo; Cottim, Joana; Morais, Isabel (Sensos-e, 2019)
Portuguese Sign Language (LGP) deaf teachers meet regularly at the Portuguese Deaf Association to develop a scientific and pedagogical basis for LGP teaching, especially as a first language to deaf students in bilingual schools. LGP grammar is one of the four study axes of the curricular program and is also one of the less defined. In order to overcome this fact, describing LGP Grammar has become a major concern for LGP deaf teachers. When doing so, this group of native LGP speakers, linguistically aware of their language characteristics, realized that verb types in LGP were not properly classified for the purpose of teaching it. After analysing different LGP syntactic structures according to argument selection of verbal typology defined in other sign languages (SL), as well as in spoken Portuguese (LP), it was clear that neither system could fully match the variability of LGP verbs. Therefore, we propose a blended classification of LGP verbs, where arguments within LP verbal system fit in general SL verb types. This new classification questions a few concepts, such as the one for indirect or oblique object, and shows the need for a different terminology in relation to argument structure in LGP. Artigo Completo